Copper-based catalyst, preparation method thereof and synthesis method of 3-hydroxybutanone
By using copper-based catalyst prepared by deposition and heat treatment of copper mesh, the anaerobic dehydrogenation reaction of 2,3-butanediol was catalyzed, and the problems of low yield, high cost and high safety risks in the existing 3-hydroxybutane production methods were solved, achieving efficient and low-cost 3-hydroxybutane preparation.
Patent Information
- Application Number
- CN202411495615.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-15
AI Technical Summary
The existing 3-hydroxybutanone production methods have problems such as low yield, high production costs and high operating safety risks. Especially when using the acetaldehyde catalytic method, the volatile acetaldehyde results in the loss of raw materials during transportation and operation, and the thiazole-based onium salts are unstable, which increases production costs and affects product quality.
A copper mesh is used as the substrate, and a copper-based catalyst is prepared by cyclic voltammetry deposition and heat treatment, which is used to catalyze the anaerobic dehydrogenation reaction of 2,3-butanediol and prepare 3-hydroxybutaneone. The process is simple to operate, has low production cost, and has better stability and specific surface area of the copper-based catalyst.
It achieves high conversion and selectivity of 3-hydroxybutanone, reduces production energy consumption and safety risks, and is suitable for large-scale industrial production.
Smart Images

Figure CN119824462A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis, and in particular to a copper-based catalyst and a preparation method thereof, and a synthesis method of 3-hydroxybutanone. Background Art
[0002] 3-Hydroxybutanone, also known as acetoin, is a compound with a milky aroma. It has a very high application value and is widely used in the food field, for example, as a flavor enhancer for coffee, nuts, chocolate, dairy products and alcoholic beverages. At the same time, 3-Hydroxybutanone can also be used as an important tobacco additive to improve tobacco quality. In addition, in the fields of medicine and chemistry, since 3-Hydroxybutanone contains active groups such as hydroxyl and carbonyl, it can be used as a raw material for the synthesis of drug intermediates and the development of multifunctional materials. At present, the 3-Hydroxybutanone products circulating in the international market are mainly produced by JM Company in the United States, BASF Company in Germany and Cinda Company in Japan. Some domestic companies produce them, but they cannot meet the needs of the domestic and international markets.
[0003] At present, the main industrial production methods of 3-hydroxybutanone include microbial fermentation and chemical synthesis. The Chinese patent with publication number CN111705027A constructs a genetically engineered strain, which is cultured in a fermenter for 96 hours and uses a wide range of biomass energy (glucose, sucrose, etc.) as raw materials. The production efficiency of 3-hydroxybutanone is 0.7g·L -1 ·h -1 , but when industrialized, there is still a problem that the output and production cost cannot match. The production of 3-hydroxybutanone at home and abroad is mainly based on chemical synthesis. The Chinese patent with publication number CN1562934A adopts acetaldehyde catalysis. Without the participation of other solvents, thiazole onium salts are selected as catalysts, which directly realizes the preparation of 3-hydroxybutanone by acetaldehyde catalysis. The best yield of 3-hydroxybutanone is 90%, and the purity is more than 98%. However, acetaldehyde is volatile, and there is a problem of raw material loss during transportation and operation, which increases the safety risk of operation; thiazole onium salts are unstable and often require a large excess, and thiazole onium salts have a peculiar smell when decomposing and sulfur-containing impurities are difficult to remove, which increases the production cost and seriously affects the product quality of 3-hydroxybutanone.
[0004] The selective oxygen-free dehydrogenation of 2,3-butanediol to prepare 3-hydroxybutanone has high atomic utilization, high product selectivity, is green and environmentally friendly, easy to separate and continuous, and can greatly reduce production energy consumption and safety risks, which is of great significance. The related prior art uses aluminosilicate-supported copper catalysts to catalyze the dehydrogenation of 2,3-butanediol. During the preparation process, auxiliary metals, alkali metals and ketone additives need to be added. The catalyst preparation process is complicated and the production cost is high. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a copper-based catalyst and a preparation method thereof, and a synthesis method of 3-hydroxybutanone. The preparation method provided by the present invention is simple to operate and has low production cost.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A method for preparing a copper-based catalyst comprises the following steps:
[0008] Using a copper mesh as the positive electrode and the negative electrode, and a metal salt mixture as the electrolyte, a catalyst precursor is obtained by deposition on the copper mesh using cyclic voltammetry under the condition of an external power supply;
[0009] thermally treating the catalyst precursor to obtain the copper-based catalyst;
[0010] The metal salt mixture includes a first metal salt and a second metal salt;
[0011] The first metal salt is a zinc salt or a magnesium salt;
[0012] The second metal salt is an aluminum salt, a gallium salt or a chromium salt.
[0013] Preferably, the molar ratio of the first metal salt to the second metal salt in the metal salt mixture is 10:1.
[0014] Preferably, the concentration of the first metal salt in the metal salt mixture is 0.05-0.15 mol / L.
[0015] Preferably, the first metal salt and the second metal salt are both nitrates.
[0016] Preferably, the purity of the copper mesh is 99.99%.
[0017] Preferably, the parameters of the cyclic voltammetry method include: a current density of 5 to 10 mA / cm 2 , the single cycle time is 20 to 40 seconds, and the number of cycles is 200 to 400.
[0018] Preferably, the heat treatment is carried out in an atmosphere of air, nitrogen or argon, at a temperature of 300 to 600° C., for a time of 1.5 to 2.5 hours.
[0019] The present invention also provides a copper-based catalyst obtained by the preparation method described in the above technical solution, wherein the copper-based catalyst comprises a copper substrate, copper oxide, a first metal oxide and a second metal oxide attached to the copper substrate; the copper content in the copper-based catalyst is 1wt% to 50wt%.
[0020] The present invention also provides a method for synthesizing 3-hydroxybutanone, comprising the following steps:
[0021] 2,3-butanediol undergoes an oxygen-free dehydrogenation reaction under the action of a catalyst to obtain the 3-hydroxybutanone;
[0022] The catalyst is the copper-based catalyst described in the above technical solution.
[0023] Preferably, the temperature of the anaerobic dehydrogenation reaction is 220-280°C and the pressure is 0.1-0.5MPa;
[0024] The weight hourly space velocity of 2,3-butanediol is 0.01 to 10 h -1 .
[0025] The invention provides a method for preparing a copper-based catalyst.
[0026] (1) The preparation method provided by the present invention uses an electrochemical method to prepare a copper-based catalyst, which is simple and efficient to operate, uses less raw materials, and has low cost; and the copper-based catalyst prepared by the present invention is a monolithic catalyst, which has better stability and a larger specific surface area, is less likely to be lost than a powdered catalyst, and is easier to recover.
[0027] (2) The present invention uses a copper mesh as a substrate. The mesh structure provides conditions for the high dispersion of the first metal and the second metal, increases the dispersion of the loaded metals (the first metal and the second metal), is not easily blocked during the reaction, and improves the catalytic stability of the copper-based catalyst.
[0028] (3) The copper-based catalyst of the present invention is Cu 0 Mainly, and there is Cu 0 / Cu 1+ / Cu 2+ The layered structure, at the same time, has a higher content of Cu 0 and Cu + , and the more stable Cu 0 / + / Cu 2+ The conversion rate of 2,3-butanediol was improved.
[0029] The invention also provides a method for synthesizing 3-hydroxybutanone.
[0030] In the present invention, the copper-based catalyst prepared by the above technical scheme is used as a catalyst to catalyze the selective oxygen-free dehydrogenation of 2,3-butanediol to produce 3-hydroxybutanone, showing high 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity. The oxygen-free dehydrogenation reaction of the present invention is carried out in a fixed bed reactor or a trickle bed reactor, and continuous production can be achieved, which is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A diagram showing the actual working conditions of the preparation of the copper-based catalyst provided by the present invention;
[0032] Figure 2 A schematic diagram of the preparation of the copper-based catalyst provided by the present invention;
[0033] Figure 3 This is a graph for evaluating the reaction stability of the copper-based catalyst obtained in Example 5;
[0034] Figure 4 is the 2,3-butanediol conversion rate of the series of copper-based catalysts obtained in Example 6;
[0035] Figure 5 The selectivity of 3-hydroxybutanone of the series of catalysts obtained in Example 6;
[0036] Figure 6 This is the mapping diagram of the copper-based catalyst ZnGa-CM obtained in Example 6. DETAILED DESCRIPTION
[0037] Figure 1 This is a diagram showing the actual working conditions of the preparation of the copper-based catalyst provided by the present invention. Figure 2 Schematic diagram of the preparation of the copper-based catalyst provided by the present invention; Figure 1 and Figure 2 The preparation of the copper-based catalyst is described in detail.
[0038] The present invention provides a method for preparing a copper-based catalyst, comprising the following steps:
[0039] Using a copper mesh as the positive electrode and the negative electrode, and a metal salt mixture as the electrolyte, a catalyst precursor is obtained by deposition on the copper mesh using cyclic voltammetry under the condition of an external power supply;
[0040] thermally treating the catalyst precursor to obtain the copper-based catalyst;
[0041] The metal salt mixture includes a first metal salt and a second metal salt;
[0042] The first metal salt is a zinc salt or a magnesium salt;
[0043] The second metal salt is an aluminum salt, a gallium salt or a chromium salt.
[0044] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0045] The present invention uses a copper mesh as the positive electrode and the negative electrode, uses a metal salt mixed solution as the electrolyte, and uses cyclic voltammetry under the condition of an external power supply to perform deposition on the copper mesh to obtain a catalyst precursor.
[0046] In the present invention, the purity of the copper mesh is preferably 99.99%. In the present invention, the mesh number of the copper mesh is preferably 150 to 250 meshes, more preferably 200 meshes. In the present invention, the thickness of the copper mesh is preferably 0.05 to 0.15 mm, more preferably 0.1 mm. The present invention uses the copper mesh as a substrate, and the mesh structure provides conditions for the high dispersion of the first metal and the second metal, increases the dispersion of the loaded metal (the first metal and the second metal), is not easy to be blocked during the reaction, and improves the catalytic stability of the copper-based catalyst. In addition, the copper-based catalyst obtained by the present invention is a monolithic catalyst, which has better stability and a larger specific surface area. Compared with powdered catalysts, it is not easy to lose and is easier to recover.
[0047] In the present invention, the metal salt mixture includes a first metal salt and a second metal salt; the first metal salt is a zinc salt or a magnesium salt, preferably a zinc salt; the second metal salt is an aluminum salt, a gallium salt or a chromium salt, preferably a gallium salt. In the present invention, the first metal salt and the second metal salt are preferably nitrates, more preferably hydrated nitrates, specifically preferably zinc nitrate hexahydrate, magnesium nitrate, aluminum nitrate nonahydrate, gallium nitrate or chromium nitrate. In the present invention, in the metal salt mixture, the combination of the first metal salt and the second metal salt is preferably a combination of zinc salt and gallium salt, a combination of magnesium salt and aluminum salt, or a combination of zinc salt and aluminum salt. In the present invention, during the deposition process, nitrate will be converted into nitrite, and OH will be generated at the same time. - , which is more conducive to the metal ions forming hydroxides and depositing on the surface of the copper mesh. Compared with sulfates and chlorides, nitrates are used, and there are more hydroxides in the electrolyte, which helps to attach more active sites. In the present invention, the ratio of the amount of the first metal salt and the second metal salt in the metal salt mixture is preferably 10:1. In the present invention, the concentration of the first metal salt in the metal salt mixture is preferably 0.05-0.15 mol / L, and specifically preferably 0.05 mol / L, 0.1 mol / L or 0.15 mol / L. In the present invention, the preparation method of the metal salt mixture preferably includes: dissolving the first metal salt and the second metal salt in water, and performing ultrasonic treatment to obtain the metal salt mixture. In the present invention, the water is preferably deionized water. In the present invention, the frequency of the ultrasonic treatment is preferably 53 Hz, and the time is preferably 30 min. In the present invention, the first metal salt can make the catalytic system produce more CuZn interfaces, promote the further progress of the reaction, and the second metal salt acts as an electron promoter to better disperse the active sites evenly.
[0048] In the present invention, the parameters of the cyclic voltammetry method include: the current density is preferably 5 to 10 mA / cm 2 , preferably 5 mA / cm 2 , 6mA / cm 2 , 7mA / cm 2, 8mA / cm 2 , 9mA / cm 2 or 10mA / cm 2 ; The single cycle time is preferably 20 to 40 seconds, and more preferably 20 seconds, 30 seconds or 40 seconds; The number of cycles is preferably 200 to 400, and more preferably 200, 300 or 400. In the present invention, the deposition by cyclic voltammetry can double the preparation efficiency in the preparation process.
[0049] In the present invention, the deposition is preferably carried out in a specific reaction pool, and the size of the specific reaction pool is preferably 6cm*3cm*6cm. In the present invention, the use of the specific reaction pool can further amplify and improve the single-time yield.
[0050] After the deposition is completed, the present invention preferably further comprises washing and drying the obtained product in sequence. In the present invention, the washing preferably comprises washing with water and washing with ethanol in sequence, the reagent for the water washing is preferably deionized water, the time for the water washing is preferably 15 minutes, and the water washing is preferably carried out under ultrasonic conditions. In the present invention, the reagent for the ethanol washing is preferably ethanol, the time for the ethanol washing is preferably 15 minutes, and the ethanol washing is preferably carried out under ultrasonic conditions. In the present invention, the temperature for the drying is preferably 60°C, the time is preferably 12 hours, and the drying is preferably carried out in an oven.
[0051] After obtaining the catalyst precursor, the present invention performs heat treatment on the catalyst precursor to obtain the copper-based catalyst.
[0052] In the present invention, the atmosphere of the heat treatment is preferably air, nitrogen or argon, and more preferably air; the temperature is preferably 300-600°C, and more preferably 300°C, 400°C, 500°C or 600°C; the heating rate to the temperature of the heat treatment is preferably 0.5-20°C / min, more preferably 0.5-5°C / min, and more preferably 1°C / min; the time is preferably 1.5-2.5h, and more preferably 2h.
[0053] In the present invention, during the heat treatment process, the metal hydroxides in the catalyst precursor are converted into metal oxides.
[0054] The present invention also provides a copper-based catalyst obtained by the preparation method described in the above technical solution. In the present invention, the copper-based catalyst includes a copper substrate, copper oxide, a first metal oxide and a second metal oxide attached to the copper substrate. In the present invention, the first metal oxide is preferably zinc oxide or magnesium oxide. In the present invention, the second metal oxide is preferably aluminum oxide, gallium oxide or chromium oxide. In the present invention, the copper content in the copper-based catalyst is 1wt% to 50wt%, preferably 6wt% to 15wt%.
[0055] The present invention also provides a method for synthesizing 3-hydroxybutanone, comprising the following steps:
[0056] 2,3-butanediol undergoes an oxygen-free dehydrogenation reaction under the action of a catalyst to obtain the 3-hydroxybutanone;
[0057] The catalyst is the copper-based catalyst described in the above technical solution.
[0058] In the present invention, the temperature of the anaerobic dehydrogenation reaction is preferably 220-280°C, preferably 240-260°C, specifically 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C; the pressure is preferably 0.1-0.5MPa, specifically 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa or 0.5MPa.
[0059] In the present invention, the weight hourly space velocity of 2,3-butanediol is preferably 0.01 to 10 h -1 , specifically 0.1h -1 .
[0060] In the present invention, the oxygen-free dehydrogenation reaction is preferably carried out in a fixed bed reactor or a trickle bed reactor.
[0061] The copper-based catalyst and its preparation method, and the synthesis method of 3-hydroxybutanone provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0062] Example 1
[0063] The current density parameters were optimized. Al(NO3)3·9H2O and Zn(NO3)2·6H2O were dissolved in 100 mL of deionized water and ultrasonicated continuously at 53 Hz for 30 min in an ultrasonic bath to obtain a metal salt mixture with a concentration of 0.01 mol / L aluminum nitrate and 0.1 mol / L zinc nitrate, which was used as the electrolyte. In a customized catalyst synthesis device, the current density was 5 mA / cm 2 , 6mA / cm 2 , 7mA / cm2 , 8mA / cm 2 , 9mA / cm 2 , 10mA / cm 2 The single deposition time was 40 s, the number of cycles was 400, and the total number of s was 16000. After the synthesis, it was ultrasonically washed with deionized water and ethanol for 15 min respectively. After washing, it was placed in an oven at 60 °C for 12 h to obtain a catalyst precursor.
[0064] The catalyst precursor was heat treated at 400°C in an air atmosphere at a rate of 1°C / min for 2 h to obtain copper-based catalysts named ZnAl-CM-5mA, ZnAl-CM-6mA, ZnAl-CM-7mA, ZnAl-CM-8mA, ZnAl-CM-9mA and ZnAl-CM-10mA.
[0065] The obtained series of copper-based catalysts were used to carry out oxygen-free dehydrogenation reaction of 2,3-butanediol to prepare 3-hydroxybutanone under the conditions (pressure, temperature and weight hourly space velocity) shown in Table 1. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of the obtained copper-based catalysts are shown in Table 1.
[0066] Table 1 Reaction conditions and test results of the series of catalysts obtained in Example 1
[0067] catalyst pressure temperature Weight Hourly Space Speed Conversion rate Selectivity ZnAl-CM-5mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 77% 76% ZnAl-CM-6mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 80% 78% ZnAl-CM-7mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 84% 79% ZnAl-CM-8mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 88% 87% ZnAl-CM-9mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 86% 85% ZnAl-CM-10mA 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 82% 80%
[0068] From Table 1, we can see that the optimal current density is 8mA / cm 2 .
[0069] Example 2
[0070] The parameters of the number of cycles were optimized. Al(NO3)3·9H2O and Zn(NO3)2·6H2O were dissolved in 100 mL of deionized water and ultrasonicated continuously for 30 min at 53 Hz in an ultrasonic pool to obtain a metal salt mixture with an aluminum nitrate concentration of 0.01 mol / L and a zinc nitrate concentration of 0.1 mol / L, which was used as the electrolyte. In a customized catalyst synthesis device, the current density was 8 mA / cm 2 The single deposition time was 40 s, the number of cycles was 200, 300, and 400, with a total of 8000 s, 12000 s, and 16000 s. After the synthesis, it was ultrasonically washed with deionized water and ethanol for 15 min respectively. After washing, it was placed in an oven at 60 °C for 12 h to obtain a catalyst precursor.
[0071] The catalyst precursor was heat treated at 400°C for 2 h in an air atmosphere at a temperature of 1°C / min to obtain copper-based catalysts named ZnAl-CM-200, ZnAl-CM-300 and ZnAl-CM-400.
[0072] The obtained series of copper-based catalysts were used to carry out oxygen-free dehydrogenation reaction of 2,3-butanediol to prepare 3-hydroxybutanone under the conditions (pressure, temperature and weight hourly space velocity) shown in Table 2. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of the obtained copper-based catalysts are shown in Table 2.
[0073] Table 2 Reaction conditions and test results of the series of catalysts obtained in Example 2
[0074] catalyst pressure temperature Weight Hourly Space Speed Conversion rate Selectivity ZnAl-CM-200 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 67% 62% ZnAl-CM-300 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 71% 69% ZnAl-CM-400 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 88% 87%
[0075] It can be seen from Table 2 that the optimal number of cycles is 400.
[0076] Example 3
[0077] The single deposition time parameters were optimized. Al(NO3)3·9H2O and Zn(NO3)2·6H2O were dissolved in 100mL of deionized water and ultrasonicated continuously for 30min at 53Hz in an ultrasonic bath to obtain a metal salt mixture with an aluminum nitrate concentration of 0.01mol / L and a zinc nitrate concentration of 0.1mol / L, which was used as an electrolyte. In a customized catalyst synthesis device, the current density was 8mA / cm 2 The single deposition time was 20s, 30s, and 40s, the number of cycles was 400 times, and the total was 8000s, 12000s, and 16000s. After the synthesis, it was ultrasonically washed with deionized water and ethanol for 15min respectively. After washing, it was placed in an oven at 60°C for 12h to obtain a catalyst precursor.
[0078] The catalyst precursor was heat treated at 400°C for 2 h in an air atmosphere at a temperature of 1°C / min to obtain copper-based catalysts named ZnAl-CM-20, ZnAl-CM-30 and ZnAl-CM-40.
[0079] The obtained series of copper-based catalysts were used to carry out oxygen-free dehydrogenation reaction of 2,3-butanediol to prepare 3-hydroxybutanone under the conditions (pressure, temperature and weight hourly space velocity) shown in Table 3. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of the obtained copper-based catalysts are shown in Table 3.
[0080] Table 3 Reaction conditions and test results of the series of catalysts obtained in Example 3
[0081] catalyst pressure temperature Weight Hourly Space Speed Conversion rate Selectivity ZnAl-CM-20 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 61% 59% ZnAl-CM-30 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 73% 70% ZnAl-CM-40 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 88% 87%
[0082] It can be seen from Table 3 that the optimal single deposition time is 40s.
[0083] Example 4
[0084] The optimization of zinc nitrate concentration in the metal salt mixture is as follows: 0.0015 mol, 0.001 mol, 0.0005 mol Al(NO3)3·9H2O and 0.015, 0.01, 0.005 mol Zn(NO3)2·6H2O are dissolved in 100 mL of deionized water, and then ultrasonicated in an ultrasonic bath at 53 Hz for 30 min to obtain a metal salt mixture with an aluminum nitrate concentration of 0.015 mol / L and a zinc nitrate concentration of 0.15 mol / L (referred to as 0.15); a metal salt mixture with an aluminum nitrate concentration of 0.01 mol / L and a zinc nitrate concentration of 0.1 mol / L (referred to as 0.1); and a metal salt mixture with an aluminum nitrate concentration of 0.005 mol / L and a zinc nitrate concentration of 0.05 mol / L (referred to as 0.05). In a customized catalyst synthesis device, the current density was 8 mA / cm 2 The single deposition time was 40 s, the number of cycles was 400, and the total number of cycles was 16,000 s. After the synthesis, the catalyst was ultrasonically washed with deionized water and ethanol for 15 min respectively. After washing, it was placed in an oven at 60°C for 12 h to obtain a catalyst precursor.
[0085] The catalyst precursor was heat treated at 400°C for 2 h in an air atmosphere at a rate of 1°C / min to obtain copper-based catalysts named ZnAl-CM-0.15, ZnAl-CM-0.1 and ZnAl-CM-0.05.
[0086] The obtained series of copper-based catalysts were used to carry out an oxygen-free dehydrogenation reaction of 2,3-butanediol to prepare 3-hydroxybutanone under the conditions (pressure, temperature and weight hourly space velocity) shown in Table 4. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of the obtained copper-based catalysts are shown in Table 4.
[0087] Table 4 Reaction conditions and test results of the series of catalysts obtained in Example 4
[0088] catalyst pressure temperature Weight Hourly Space Speed Conversion rate Selectivity ZnAl-CM-0.15 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 86% 85% ZnAl-CM-0.1 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 88% 87% ZnAl-CM-0.05 0.1MPa 250℃ <![CDATA[0.1h -1 ]]> 74% 71%
[0089] It can be seen from Table 4 that the optimal concentration of zinc nitrate in the metal salt mixture is 0.1 mol / L.
[0090] In summary, the optimal preparation conditions for the copper-based catalyst include: the concentration of the first metal salt in the metal salt mixture is 0.1 mol / L, the current density is 8 mA / cm 2 , the single deposition time is 40s and the number of cycles is 400 times.
[0091] Example 5
[0092] The copper-based catalyst ZnAl-CM was prepared under the optimal preparation conditions obtained in the above example. The specific steps were as follows: Al(NO3)3·9H2O and Zn(NO3)2·6H2O were dissolved in 100 mL of deionized water, and ultrasonicated continuously at 53 Hz for 30 min in an ultrasonic bath to obtain a metal salt mixture with an aluminum nitrate concentration of 0.01 mol / L and a zinc nitrate concentration of 0.1 mol / L, which was used as an electrolyte. In a customized catalyst synthesis device, the current density was 8 mA / cm 2 The single deposition time was 40 s, the number of cycles was 400, and the total number of s was 16000. After the synthesis, it was ultrasonically washed with deionized water and ethanol for 15 min respectively. After washing, it was placed in an oven at 60 °C for 12 h to obtain a catalyst precursor.
[0093] The catalyst precursor was heat treated at 400° C. for 2 h at a temperature of 1° C. / min under air atmosphere to obtain a copper-based catalyst.
[0094] The copper-based catalyst obtained in Example 5 was heated at a pressure of 0.1 MPa, a temperature of 250°C and a weight hourly space velocity of 0.1 h -1 Under the conditions of , 2,3-butanediol was subjected to oxygen-free dehydrogenation to prepare 3-hydroxybutanone, and the reaction stability was evaluated. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of the obtained copper-based catalyst were as follows: Figure 3 shown.
[0095] from Figure 3 It can be seen that the copper-based catalyst ZnAl-CM prepared under the optimal preparation conditions can maintain stability for about 100 hours while maintaining 87% conversion and 88% selectivity.
[0096] Example 6
[0097] Copper-based catalysts ZnAl-CM, ZnGa-CM, ZnCr-CM, MgAl-CM, MgGa-CM and MgCr-CM were prepared under the optimal preparation conditions, respectively. Similar to Example 5, the only difference was that the types of the first metal salt and the second metal salt were replaced.
[0098] The obtained series of catalysts were heated at a pressure of 0.1 MPa, a temperature of 250°C and a weight hourly space velocity of 0.1 h -1 Under the conditions of , 2,3-butanediol was subjected to oxygen-free dehydrogenation to prepare 3-hydroxybutanone, and the reaction stability was evaluated. The 2,3-butanediol conversion rate and 3-hydroxybutanone selectivity of each copper-based catalyst were as follows: Figure 4 and Figure 5 shown.
[0099] Figure 4 is the conversion rate of 2,3-butanediol of the obtained series of copper-based catalysts, Figure 5 is the 3-hydroxybutanone conversion rate of the obtained series of copper-based catalysts.
[0100] from Figure 4 It can be seen that under the same conditions, in the performance evaluation of 2,3-butanediol conversion rate, the copper-based catalysts ZnGa-CM and MgAl-CM are superior to the copper-based catalyst ZnAl-CM, which is approximately 2% higher.
[0101] from Figure 5 It can be seen that under the same conditions, in the performance evaluation of 3-hydroxybutanone selectivity, the copper-based catalysts ZnGa-CM and MgAl-CM are superior to the copper-based catalyst ZnAl-CM catalyst, which is approximately 2 to 3% higher.
[0102] Figure 6 This is the mapping diagram of the copper-based catalyst ZnGa-CM obtained in Example 6. Figure 6 It can be seen that the Zn / Ga elements are relatively evenly present on the copper mesh skeleton, which also represents the successful construction of the ZnGa-CM catalyst system.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a copper-based catalyst, characterized in that: The following steps are involved: Using a copper mesh as the positive electrode and the negative electrode, and a metal salt mixture as the electrolyte, a catalyst precursor is obtained by deposition on the copper mesh using cyclic voltammetry under the condition of an external power supply; thermally treating the catalyst precursor to obtain the copper-based catalyst; The metal salt mixture includes a first metal salt and a second metal salt; The first metal salt is a zinc salt or a magnesium salt; The second metal salt is an aluminum salt, a gallium salt or a chromium salt.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the first metal salt to the second metal salt in the metal salt mixture is 10:
1.
3. The preparation method according to claim 1 or 2, characterized in that: The concentration of the first metal salt in the metal salt mixture is 0.05-0.15 mol / L.
4. The preparation method according to claim 1, characterized in that: The first metal salt and the second metal salt are both nitrates.
5. The preparation method according to claim 1, characterized in that: The purity of the copper mesh is 99.99%.
6. The preparation method according to claim 1, characterized in that: The parameters of the cyclic voltammetry method include: a current density of 5 to 10 mA / cm 2 , the single cycle time is 20 to 40 seconds, and the number of cycles is 200 to 400.
7. The preparation method according to claim 1, characterized in that: The heat treatment is carried out in an atmosphere of air, nitrogen or argon, at a temperature of 300 to 600° C., for a time of 1.5 to 2.5 hours.
8. The copper-based catalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The copper-based catalyst comprises a copper substrate, copper oxide, a first metal oxide and a second metal oxide attached to the copper substrate; the content of copper in the copper-based catalyst is 1 wt% to 50 wt%.
9. A method for synthesizing 3-hydroxybutanone, characterized in that: The following steps are involved: 2,3-butanediol undergoes an oxygen-free dehydrogenation reaction under the action of a catalyst to obtain the 3-hydroxybutanone; The catalyst is the copper-based catalyst according to claim 8.
10. The synthesis method according to claim 9, characterized in that The temperature of the oxygen-free dehydrogenation reaction is 220-280°C and the pressure is 0.1-0.5MPa; The weight hourly space velocity of 2,3-butanediol is 0.01 to 10 h -1 .
Citation Information
Patent Citations
Method for producing acetoin by utilizing fermentation of microbes
CN111705027A
Method for synthesizing Yiyuyin through catalysis of acetaldehyde
CN1562934A